A performance analysis of a cloud database on mobile devices - Sylwester Kot; Jakub Smołka (Journal of Computer Sciences Institute)
The article presents a performance analysis of Firebase cloud database. Two services, namely Realtime Database and Cloud Firestore, are examined, and their query speed are compared to those of the local SQLite database. Basic CRUD operations were examined, taking into account the number of records in the database, the size of individual records and the complexity of the database structure. Upon completion of the research, it was concluded that Realtime Database outperforms Cloud Firestore and cloud databases are slower than the local database when it comes to operations on a single record. However, when working with a larger volume of data, cloud database can achieve better results than SQLite. The accuracy of the outcome is also influenced by the stability of the network connection and the distance from the cloud server.